Does Information and Communications Technology (ICT) Development Foster Economic Growth of ASEAN5 +3 Countries? - Syuen , Wong Ee; Ab-Rahim, Rossazana (Asian Journal of Empirical Research, 2020)
Globally, digital technologies affect lifestyles, norms and business restructuring models. Correspondingly, it plays a significant role in fostering the economic growth of Association of South East Asian Nations (ASEAN) as well as Asian countries at large. This study aims to investigate the impact of ICT development on the economic growth of the ASEAN5 +3 nations over the period of 2011 to 2018. ASEAN5+3 comprises of eight nations namely Malaysia, Singapore, Philippines, Thailand, Indonesia, China, South Korea and Japan. The methodologies applied in this study include panel data regression analysis and several diagnostic tests such as the Hausman test and the Breusch-Pagan Lagrange multiplier (BPLM) test. The empirical results suggest there is a positive significant relationship between ICT development and economic growth among the ASEAN5 +3 countries. This relationship can be further strengthened through various policy implementations such as governmental investments. The results of this study imply that these Asian countries are growing in consistence with information technology (IT)-led development.